2019
DOI: 10.1101/622142
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

When does gene flow facilitate evolutionary rescue?

Abstract: 9Experimental and theoretical studies have highlighted the impact of gene flow on the prob-10 ability of evolutionary rescue in structured habitats. Mathematical modelling and simulations 11 of evolutionary rescue in spatially or otherwise structured populations showed that interme-12 diate migration rates can often maximize the probability of rescue in gradually or abruptly 13 deteriorating habitats. These theoretical results corroborate the positive effect of gene flow 14 on evolutionary rescue that has been… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 53 publications
1
18
0
Order By: Relevance
“…Indeed, there are several cases in Fiji in which small islands have distinct species from the large islands (honeyeaters, Andersen et al., 2014; monarch‐flycatchers, Andersen et al., 2015; fruit‐doves, Cibois et al., 2014). Despite the potential for genetic swamping, this asymmetric gene flow could also facilitate genetic rescue of small island populations in deteriorating conditions (Brown & Kodric‐Brown, 1977; Tomasini & Peischl, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, there are several cases in Fiji in which small islands have distinct species from the large islands (honeyeaters, Andersen et al., 2014; monarch‐flycatchers, Andersen et al., 2015; fruit‐doves, Cibois et al., 2014). Despite the potential for genetic swamping, this asymmetric gene flow could also facilitate genetic rescue of small island populations in deteriorating conditions (Brown & Kodric‐Brown, 1977; Tomasini & Peischl, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a recent study of insular avian gene flow found more migrants from a larger to a smaller island (Cooper & Uy, 2017). This higher rate of gene flow suggests increased genetic homogenization between insular populations and could facilitate genetic rescue of smaller populations (Bell, 2017; Brown & Kodric‐Brown, 1977; Tomasini & Peischl, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In general, expansion load increases under conditions that favour genetic surfing, such as small population size, high growth and low migration rate from neighbour populations (Klopfstein et al, 2006; Peischl et al, 2013). Conversely, mechanisms favouring increased migration to range‐front populations throughout the course of range expansion, such as the evolution of higher dispersal rates at the leading edge (“spatial sorting”; Shine et al, 2011), could reduce genetic drift and “rescue” populations from incurring expansion load (Peischl & Gilbert, 2020; Tomasini & Peischl, 2020). In the same way, when range expansions occur along environmental gradients, the expansion is slowed by the need for colonizing populations to adapt to the novel local environment.…”
Section: Introductionmentioning
confidence: 99%
“…the adaptive response and recovery from reduced absolute fitness due to environmental change. Also, Tomasini & Peischl (2019) investigated the effect of local adaptations on evolutionary rescue. But whether GR would lead to the loss of unique local adaptations, or whether local adaptations could affect the process of fitness restoration by GR, remain largely unexplored.…”
Section: Introductionmentioning
confidence: 99%